The Influence of Health Information System and Employee Competency on the Quality of Public Services at the Health, Population Control and Family Planning Office of Central Papua Province - Anita Salombe; Corvis L Rantererung; Kristian HP Lambe (Riviera Publishing, 2025)
This study aims to analyze the influence of the Health Information System and Employee Competency on the Quality of Public Services at the Central Papua Provincial Health, Population Control, and Family Planning Office. Using a quantitative approach, this study collected primary and secondary data through observation, interviews, and documentation. The study population included all employees of the Health Office with a total of 52 people, and saturated sample techniques were used to determine the sample. Data analysis was carried out by multiple linear regression using the SPSS Version 22 application. The results of the study show that the Health Information System has a significant effect on the Quality of Public Services, where the good implementation of the information system not only increases the efficiency and effectiveness of services, but also contributes to public satisfaction with health services. Employee Competence also has a positive and significant effect on the Quality of Public Services, by increasing competence through training and leadership support, employees can provide better and responsive services. Simultaneously, the Health Information System and Employee Competency have an effect on the Quality of Public Services, where the combination of the two creates an environment that supports quality health services. This study concludes that the integration between efficient information systems and competent employees is the key to achieving optimal public service goals at the Central Papua Provincial Health, Population Control, and Family Planning Office.